2020
DOI: 10.1093/jmcb/mjaa058
|View full text |Cite
|
Sign up to set email alerts
|

Adaptor protein APPL1 links neuronal activity to chromatin remodeling in cultured hippocampal neurons

Abstract: Local signaling events at synapses or axon terminals are communicated to the nucleus to elicit transcriptional responses, and thereby translate information about the external environment into internal neuronal representations. This retrograde signaling is critical to dendritic growth, synapse development, and neuronal plasticity. Here, we demonstrate that neuronal activity induces retrograde translocation and nuclear accumulation of endosomal adaptor APPL1. Disrupting the interaction of APPL1 with Importin α1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…In the present study, we found that inhibiting the expression of KLK6 led to the upregulation of Appl2, Nav2, and Nrn1 expression in neurons, which may be the potential mechanism of KLK6 inhibition to protect neuronal synaptic structures from damage. Appls are multifunctional adaptor proteins; Appl2 is an isoform of Appl1 that mediates the PI3K/Akt cascade to promote cortical neuronal survival (Wu et al 2020) and also contributes to the modulation of synaptic plasticity via coupling neuronal activity with chromatin remodeling (Liu et al 2017). Thus, it is reasonable that Appl2 is involved in siRNA-KLK6mediated synaptic structural recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that inhibiting the expression of KLK6 led to the upregulation of Appl2, Nav2, and Nrn1 expression in neurons, which may be the potential mechanism of KLK6 inhibition to protect neuronal synaptic structures from damage. Appls are multifunctional adaptor proteins; Appl2 is an isoform of Appl1 that mediates the PI3K/Akt cascade to promote cortical neuronal survival (Wu et al 2020) and also contributes to the modulation of synaptic plasticity via coupling neuronal activity with chromatin remodeling (Liu et al 2017). Thus, it is reasonable that Appl2 is involved in siRNA-KLK6mediated synaptic structural recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, dendritic spine-located APPL1 senses synaptic activity and is translocated to the nucleus upon neuronal activation, where it facilitates transcription necessary for late-phase LTP maintenance. Blocking APPL1 activity impairs late LTP but not LTP induction nor early LTP [ 62 ].…”
Section: Central Adiponectin Signaling Regulates Cellular Metabolism ...mentioning
confidence: 99%